Thermophilic grouting material and preparation method thereof
Patent Information
- Application Number
- CN202610971306.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-27
AI Technical Summary
并在阻水层内设置集水层及抽吸装置,用于将集水层内的积水抽吸至采空区外侧,以解决煤矿地下水库坝体防渗效果较差的问题;中国专利文件CN102767395B公开了一种矿井地下水库的防渗方法,提出用水泥护壁层、防渗土工布和水泥防渗层组合在一起构成防渗墙来进行防渗
[0014](Ⅰ)本发明中的注浆材料的趋温性使浆液在注入初期低温环境下保持良好流动性,易于填充采空区复杂裂隙;随着环境温度上升,如深部采空区高温环境,温敏聚合物与温度响应型添加剂协同作用,加速浆液固化;在温度跨度较大的采空区作业中,本发明的注浆材料的注浆效率较传统材料明显提升,兼顾了流动性与凝结时间,减少因浆液性能不稳定导致的返工与设备故障,显著提高施工效率。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coal mining water resource protection and utilization technology, and relates to grouting materials, specifically a temperature-sensitive grouting material and its preparation method. Background Technology
[0002] Coal mine underground water reservoirs are a new type of hydraulic structure that uses the goaf to store water, employs coal pillars and artificial dams to form a water-retaining structure, and is equipped with water diversion facilities. Some coal pillar dams are formed by leaving sections of coal pillars. During mining, they suffer initial damage due to the pressure of the pre-support structure. After water storage, they continue to suffer damage due to water erosion and overburden pressure, jeopardizing the safe operation of the coal mine underground water reservoir. For high-extraction mining processes, the pre-support pressure on the coal pillars is significantly increased, resulting in a wider range of initial damage. Simultaneously, the temperature distribution around the coal mine underground water reservoir and the goaf is uneven. Some areas are warmer due to geothermal influence, while others are cooler due to ventilation and water bodies, creating a complex temperature environment that further exacerbates the degradation of traditional grouting materials and affects the reinforcement and seepage prevention effect. To reduce the degree of damage to the coal pillar dams before and after mining in high-extraction mining processes and to ensure the safety and stability of the coal pillar dams during the operation of the coal mine underground water reservoir, it is urgent to propose a reinforcement and seepage prevention method for coal pillar dams in coal mine underground water reservoirs that is suitable for complex temperature environments.
[0003] In existing technologies, such as Chinese patent document CN107237651B, a multi-layer grouting anti-seepage reinforcement method for underground reservoirs and dams in coal mines is disclosed. This method involves sequentially spraying concrete slurry and silica sol onto the walls of the roadways on both sides of the underground reservoir and the retreat roadway, forming a concrete and silica sol spray layer. Then, multiple shallow and deep grouting holes are constructed and sealed for grouting. The grouting material is a nano-scale inorganic material. Chinese patent document CN114033489B discloses an anti-seepage system for underground reservoir dams in coal mines, proposing the construction of a water-blocking layer on the side of the coal pillar dam adjacent to the goaf to isolate the underground reservoir from the goaf. A water collection layer and a suction device are installed inside the water-blocking layer to pump the accumulated water in the water collection layer to the outside of the goaf, so as to solve the problem of poor seepage prevention effect of the underground water reservoir dam in coal mines; Chinese patent document CN102767395B discloses a seepage prevention method for underground water reservoirs in mines, proposing to use a combination of cement wall protection layer, seepage-proof geotextile and cement seepage-proof layer to form a seepage-proof wall for seepage prevention.
[0004] These patents may involve different technical solutions and methods, but they have shortcomings. First, the multi-layer grouting anti-seepage reinforcement method is not suitable for the anti-seepage of coal pillar dams in underground water reservoirs of coal mines with high mining height, and cannot effectively prevent seepage above the side of the coal pillar dam adjacent to the goaf. Second, the construction of a water-blocking layer on the side of the coal pillar dam adjacent to the goaf is a large-scale and complex project that cannot meet the actual needs on site. Third, the cement and concrete used are themselves microporous materials with cracks and fissures. Black clay not only has microcracks and fissures, but these cracks and fissures also develop and expand over time. Fourth, due to construction limitations, geotextiles cannot be laid across the entire tunnel surface. In addition, after the geotextile is installed, there will always be some defects, including poor splicing quality leading to seams, punctures during construction, damage from the underlying fill layer, and uneven tearing of the geotextile on the tunnel wall. These defects directly affect the seepage prevention performance of the dam. Fifth, traditional grouting materials do not have temperature response capabilities. In the complex temperature environment of underground coal mine reservoirs, their fluidity decreases sharply at low temperatures, making it difficult to fill microcracks. At high temperatures, their performance deteriorates and their strength decreases, making it impossible to guarantee the reinforcement and seepage prevention effect in the long term. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a temperature-responsive grouting material and its preparation method, thereby solving the technical problem that the temperature response capability of grouting materials in the existing technology needs to be further improved.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution.
[0007] A temperature-responsive grouting material, comprising, by weight, the following raw materials: 45%–60% base cementitious material, 11%–23% temperature-sensitive polymer, 5%–11% temperature-responsive additive, 5%–10% flame retardant, 3%–7% anti-permeability agent, 1%–3% water-reducing agent, and the balance being water, wherein the sum of the weight parts of the raw materials is 100%; the base cementitious material includes sulfoaluminate cement; the temperature-sensitive polymer includes graft-modified poly(N-isopropylpropylene). The thermosensitive polyurethane is modified with amide and nanocomposite. The grafted poly(N-isopropylacrylamide) is prepared by grafting polyethylene glycol onto poly(N-isopropylacrylamide), wherein the poly(N-isopropylacrylamide) has a carboxyl or hydroxyl group at its end, and the low critical solution temperature of the grafted poly(N-isopropylacrylamide) is 25-40°C. The nanomaterial used in the preparation of the thermosensitive polyurethane is nano-TiO2 particles. The temperature-responsive additives include low-temperature accelerators and high-temperature regulators.
[0008] The present invention also protects a method for preparing the temperature-sensitive grouting material as described above, the method specifically including the following steps.
[0009] Step 1: Raw material pretreatment.
[0010] The base cementitious material, flame retardant, and anti-permeability agent are ground to a particle size of less than or equal to 100 μm to obtain the treated base cementitious material, the treated flame retardant, and the treated anti-permeability agent.
[0011] Step 2: Mix and stir.
[0012] Add water, the treated base cementitious material obtained in step one, the treated flame retardant, and the treated impermeable agent to a planetary mixer and stir at a speed of 200-300 r / min for 5-8 min; then add water-reducing agent and continue stirring for 3-5 min; then add grafted modified polyN-isopropylacrylamide, nanocomposite modified thermosensitive polyurethane, low-temperature accelerator, and high-temperature regulator in sequence, increase the stirring speed to 400-500 r / min, and stir for 15-20 min to obtain a temperature-sensitive grouting material.
[0013] Compared with the prior art, the present invention has the following technical effects.
[0014] (I) The thermotropic properties of the grouting material in this invention enable the grout to maintain good fluidity in the low-temperature environment at the initial stage of injection, making it easy to fill complex fissures in the goaf. As the ambient temperature rises, such as in the high-temperature environment of deep goaf, the thermosensitive polymer and temperature-responsive additives work synergistically to accelerate the solidification of the grout. In goaf operations with a large temperature range, the grouting efficiency of the grouting material of this invention is significantly improved compared with traditional materials, taking into account both fluidity and setting time, reducing rework and equipment failures caused by unstable grout performance, and significantly improving construction efficiency.
[0015] (II) In the low-temperature range (-20 to 25°C), the grafted modified poly(N-isopropylacrylamide) molecular chains of the grouting material of this invention are extended and in a hydrophilic state. Combined with the glycerol and nanocellulose whiskers in the low-temperature accelerator, ice crystal growth is inhibited, maintaining the fluidity of the grouting material. The flexible segments of the nanocomposite modified thermosensitive polyurethane and nano-TiO2 particles enhance the interfacial toughness and prevent brittleness. In the medium-temperature range (25 to 40°C), the grafted modified poly(N-isopropylacrylamide) dominates the response and undergoes a hydrophilic-hydrophobic phase transition near the LCST, precisely controlling the grout viscosity and curing rate. The nanocomposite modified thermosensitive polyurethane network buffers the phase transition stress and avoids structural damage. In the high-temperature range (40 to 60°C), the nanocomposite modified thermosensitive polyurethane crosslinking network inhibits high-temperature degradation. Hydroxypropyl methylcellulose and citric acid in the high-temperature regulator regulate the hydration rate and work synergistically with the hydrophobic shrinkage of the grafted modified poly(N-isopropylacrylamide) to prevent rapid setting. Through this segmented collaboration, the two polymers cover the performance requirements across the entire temperature range, resolving the performance contradictions of a single material over a wide temperature range (such as the imbalance between low-temperature fluidity and high-temperature strength), and achieving dynamic and intelligent control of the grouting material performance.
[0016] (III) The method in this invention is based on temperature-dependent design. At low temperatures, the accelerator accelerates cement hydration, enabling the grout to obtain better early strength within 48 hours. At high temperatures, the high-temperature regulator controls the hydration rate, avoiding internal stress caused by excessively rapid setting, effectively preventing cracking of the grout, ensuring the long-term support stability of the goaf, and avoiding the problems of insufficient early strength or later structural cracking that can easily occur in existing materials when the temperature changes due to uncontrollable hydration process.
[0017] (IV) The flame retardant in this invention, combined with the rapid curing characteristics of temperature-sensitive materials in high-temperature environments, effectively suppresses fire risks; the water-reducing agent, in synergy with the temperature-sensitive polymer, ensures optimized material flowability at different temperatures; and the anti-permeability agent, in conjunction with the temperature-sensitive material, forms a dense structure that resists groundwater erosion. Compared to traditional materials, the overall performance is significantly improved, meeting multiple engineering requirements in complex environments.
[0018] (V) The grouting material of the present invention enables grouting operations in coal mine goaf areas to be carried out in different seasons and at different depths. The precise control of the temperature-sensitive range of 25-40℃ of the present invention can ensure that the grout has the best fluidity when the construction is carried out at normal temperature. When the grout is injected into the goaf area, if the ambient temperature rises to 30-40℃, the temperature-sensitive system accelerates the solidification by increasing the viscosity, avoiding excessive flow of the grout. If injected into a low temperature area (such as -20℃), the temperature-sensitive system works synergistically with the antifreeze component to prevent the grout from losing its plasticity due to the low temperature during the flow process.
[0019] (VI) The 25-40℃ temperature-sensitive range in this invention is the intelligent central hub for grouting materials to cope with a wide operating temperature range of -20℃ to 60℃. Through synergy with antifreeze components and high-temperature resistant components, it not only solves the defect of traditional materials having "one-size-fits-all" performance in a wide temperature range, but also achieves temperature adaptation of grouting materials throughout the entire cycle from construction to service through dynamic adjustment of temperature-sensitive phase change.
[0020] (VII) The grafted poly(N-isopropylacrylamide) in this invention dominates the precise temperature-sensitive response in the medium temperature range of 25-40°C. By grafting with polyethylene glycol, the LCST is broadened from 32°C to 25-40°C, and the molecular chain of the grafted poly(N-isopropylacrylamide) undergoes a reversible hydrophilic-hydrophobic conformational transition when the temperature changes. The nanocomposite modified temperature-sensitive polyurethane expands the adaptability of the grouting material at extreme temperatures (such as -20°C and 60°C), making up for the limitations of the grafted poly(N-isopropylacrylamide) in the non-LCST range.
[0021] (VIII) In the grouting material of this invention, at low temperatures, the modified nano-TiO2 particles are uniformly dispersed in the polyurethane, giving the grouting material good flexibility and ductility, allowing it to flow flexibly in the complex spatial structure of the low-temperature goaf and fully fill every corner. At high temperatures, the modified nano-TiO2 particles act as crosslinking points, promoting crosslinking reactions between polyurethane molecular chains, significantly improving the strength and rigidity of the grouting material, effectively supporting the goaf roof and preventing collapse. The high specific surface area and active surface of the modified nano-TiO2 particles can form chemical bonds or physical adsorption with the polyurethane molecular chains, changing the molecular aggregation state and network structure of the polymer at different temperatures, thereby affecting the mechanical properties of the material.
[0022] The specific content of the present invention will be further described in detail below with reference to the embodiments. Detailed Implementation
[0023] It should be noted that, unless otherwise specified, all equipment, components, materials, and methods in this invention adopt those commonly known in the art in the prior art. For example, the pressure testing machine adopts a known pressure testing machine, the flexural testing machine adopts a known flexural testing machine, the standard demolding tool adopts a known standard demolding tool, the planetary mixer adopts a known planetary mixer, the sulfoaluminate cement adopts a known sulfoaluminate cement, the aluminum hydroxide flame retardant adopts a known aluminum hydroxide flame retardant, the polycarboxylate superplasticizer adopts a known polycarboxylate superplasticizer, the polyN-isopropylacrylamide with carboxyl or hydroxyl groups at the end adopts a known polyN-isopropylacrylamide, the N-isopropylacrylamide monomer adopts a known N-isopropylacrylamide monomer, the organic amine adopts the commonly known organic amine in the art, and the light calcium carbonate adopts a known light calcium carbonate.
[0024] The water used in this invention is all deionized water, which is commonly known in the art.
[0025] In this invention, grafted modified poly(N-isopropylacrylamide) and nanocomposite modified thermosensitive polyurethane constitute a thermosensitive polymer; the low critical solution temperature (LCST) of the grafted modified poly(N-isopropylacrylamide) is 25-40°C; and the low temperature accelerator and the high temperature regulator constitute a temperature-responsive additive.
[0026] In this invention, the average functionality of the polyether polyols is 3.
[0027] The preparation method, demolding method, curing method, and pretreatment before performance testing of the test samples corresponding to the data in Tables 1 and 2 of this invention specifically include the following:
[0028] First, the preparation of test samples.
[0029] Using the grouting materials prepared according to the corresponding formulations in Examples 1 to 3 and Comparative Examples 1 to 8 as raw materials, the following were prepared: compressive / flexural strength test blocks (40mm×40mm×160mm) and frustum test blocks for impermeability testing (upper diameter 175mm, lower diameter 185mm, height 150mm); after molding, all test blocks were placed in an environment of 20±2℃ and relative humidity of 60%~80% for 24±2h. During the standing period, vibration, direct sunlight and drastic temperature fluctuations were avoided to ensure that the test blocks were initially solidified and the surface was undamaged.
[0030] Second, demolding.
[0031] After the settling period, demold using a standard demolding tool to ensure the edges and corners of the specimen are intact and the surface is free of cracks. The demolding operation must be carried out at an environment of 20±2℃ to avoid damage to the specimen structure due to sudden temperature changes.
[0032] Third, maintenance.
[0033] After demolding, the test blocks are immediately transferred to standardized curing conditions, including the following: temperature 20±1℃ (accurately controlled within ±0.5℃, using a known constant temperature and humidity curing chamber); relative humidity greater than or equal to 90% (humidity fluctuation not exceeding ±5%, maintained by a commonly used saturated salt solution); curing medium: the test blocks are completely immersed in Grade III water conforming to GB / T6682 (water to test block volume ratio not less than 5:1), with the curing water changed weekly to maintain water quality and avoid contamination; curing periods are 3 days, 7 days, and 28 days respectively. During curing, a minimum distance of 5mm must be maintained between test blocks and between the test blocks and the container wall to avoid mutual compression or adhesion; corrosive substances must not be stored in the curing chamber / room, and airflow should be avoided from directly blowing on the surface of the test blocks.
[0034] Fourth, preprocessing before performance testing.
[0035] After reaching the specified curing age (e.g., 28 days), remove the test block, gently wipe the surface moisture with a damp towel, and place it in an environment of 20±2℃ and relative humidity of 60%~80% for 30±5 minutes to allow the surface of the test block to dry naturally before conducting performance tests such as 28-day compressive strength, flexural strength, and impermeability grade.
[0036] The relevant performance parameter detection methods and standards in Examples 1 to 3 and Comparative Examples 1 to 8 of this invention are as follows.
[0037] First, compressive strength: According to the commonly used "Test Method for Strength of Cement Mortar (ISO Method)", the prepared grouting material is made into specimens of 40mm×40mm×160mm, cured under standard curing conditions to the specified age, and then the compressive strength is tested on a pressure testing machine.
[0038] Second, flexural strength: Also according to the "Test Method for Strength of Cement Mortar (ISO Method)," a flexural strength test is conducted before the compressive strength test. A load is applied to the specimen using a flexural testing machine until the specimen breaks, the failure load is recorded, and the flexural strength is calculated.
[0039] Third, fluidity: The fluidity test method in the "Technical Specification for Application of Cement-based Grouting Materials" (GB / T50448-2015), which is commonly known in this field, is adopted. Using a truncated cone mold commonly known in this field, the obtained grouting material is poured into the mold, the mold is lifted, and the diameter of the material flowing in the plane is measured. The average value of the diameters in two mutually perpendicular directions is taken as the fluidity index.
[0040] Fourth, setting time: The test was conducted in accordance with the commonly used standard in this field, "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" (GB / T1346-2011). A Vicat apparatus, also commonly used in this field, was used. The obtained grouting material was loaded into a mold, and the initial and final setting times were determined by the depth to which the probe penetrated.
[0041] Fifth, impermeability grade: The impermeability test method is based on the commonly used standard in this field, "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T50082-2009). The grouting material is prepared into a frustum-shaped specimen with an upper diameter of 175mm, a lower diameter of 185mm, and a height of 150mm. A water pressure test is conducted on a commonly used impermeability tester in this field. The impermeability grade is determined by the water pressure at which seepage begins to appear on the top surface of the specimen.
[0042] In this invention, all test data in Tables 1 and 2 are test data after the test samples (i.e. test blocks) have been cured for 28 days.
[0043] In this invention, when preparing grafted modified poly(N-isopropylacrylamide), the mass of deionized water added as solvent is 5 to 10 times the total mass of poly(N-isopropylacrylamide) and polyethylene glycol. This can promote molecular diffusion by reducing the viscosity of the system, prevent poly(N-isopropylacrylamide) from agglomerating due to excessive concentration, and ensure that the grafting reaction proceeds uniformly. The reaction temperature of 40 to 60°C ensures the catalytic activity of dicyclohexylcarbodiimide, avoids thermal oxidation of polyethylene glycol, and prevents poly(N-isopropylacrylamide) from undergoing chain transfer side reactions at high temperatures. By precisely controlling the grafting rate to be greater than or equal to 85%, the low critical solution temperature (LCST) of poly(N-isopropylacrylamide) was broadened from 32℃ to 25-40℃ after grafting modification. At the same time, the hydrophilicity of the polyethylene glycol segments improved the dispersibility of poly(N-isopropylacrylamide) in cement-based grouts, avoiding the agglomeration of temperature-sensitive polymers. This allows it to respond more precisely to temperature changes in grouting materials, achieving the functions of maintaining fluidity at low temperatures and controlling the curing rate at medium temperatures. This lays the foundation for performance adaptation in a wide temperature range of -20℃ to 60℃.
[0044] In this invention, the mass ratio of N-isopropylacrylamide monomer to initiator azobisisobutyronitrile (AIB) is set at (85–100):1. This ratio ensures that AIB provides sufficient free radicals to initiate polymerization while avoiding excessive initiator leading to rapid chain termination and molecular weight reduction. A reaction temperature of 50–65°C ensures stable decomposition of AIB while preventing premature thermosensitive phase transition or thermal degradation of the poly(N-isopropylacrylamide). A reflux reaction time of 8–12 hours allows for sufficient polymerization, resulting in a relatively uniform molecular weight distribution of the product. Evaporation of the solvent, dissolution in acetone, and precipitation in n-hexane effectively remove unreacted monomers and impurities. Vacuum drying at 25–35°C prevents high-temperature damage to the poly(N-isopropylacrylamide) structure and ensures thorough removal of moisture. By precisely controlling the reaction parameters, poly(N-isopropylacrylamide) with controllable molecular weight, high purity, and stable thermosensitive properties can be prepared.
[0045] In this invention, during the preparation of nanocomposite-modified thermosensitive polyurethane, the dosage of 3%–5% KH-550 ensures sufficient modification of the nano-TiO2 particles and avoids agglomeration. The 3%–5% content of nano-TiO2 particles modified with the silane coupling agent KH-550 achieves a balance between improving high-temperature stability and maintaining thermosensitive responsiveness. The nano-TiO2 particles modified with the silane coupling agent KH-550 suppress chain segment movement, enabling the material to exhibit freeze-thaw elasticity at -20°C, and achieving thermosensitive synergy with the grafted-modified poly(N-isopropylacrylamide) phase transition within a temperature range of 25–40°C.
[0046] In this invention, the high-temperature regulator delays fluidity loss by forming a gel network with hydroxypropyl methylcellulose at temperatures above 40°C, and the citric acid decomposes at temperatures above 60°C to accelerate the hydration of key minerals in sulfoaluminate cement to shorten the setting time. Light calcium carbonate regulates the crystallization rate by physically filling pores and reacting with citric acid to generate slightly soluble calcium citrate. The three components, in a mass ratio of (3-4):(1-2):(4-6), work together to achieve a dynamic balance between fluid protection, controllable setting, and stable strengthening of the grouting material under high-temperature conditions, thus avoiding the risk of rapid setting and pipe blockage, while ensuring early strength development and long-term structural density.
[0047] In this invention, in step two, after adding grafted modified poly(N-isopropylacrylamide), nanocomposite modified thermosensitive polyurethane, low-temperature accelerator, and high-temperature regulator, the mixture is stirred at a speed of 400-500 r / min. The strong shear force generated by the high-speed stirring promotes the full mixing of various liquid and solid components, ensuring that the thermosensitive polymer and temperature-responsive additives are uniformly dispersed in the sulfoaluminate cement system, so that the grouting material can exhibit consistent temperature-responsive properties and other excellent properties in different parts.
[0048] Following the above technical solutions, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent modifications made on the basis of the technical solutions of the present invention fall within the protection scope of the present invention.
[0049] Example 1:
[0050] This embodiment provides a temperature-responsive grouting material, which is made from the following raw materials by weight: 60% basic cementitious material, i.e., sulfoaluminate cement; 11% temperature-sensitive polymer (specifically, 8% grafted modified poly(N-isopropylacrylamide) and 3% nanocomposite modified temperature-sensitive polyurethane); 5% temperature-responsive additive (specifically, 3% low-temperature accelerator and 2% high-temperature regulator); 5% aluminum hydroxide flame retardant; 3% anti-permeability agent; 1% polycarboxylate superplasticizer; and the balance is water. The total weight of the raw materials is 100%.
[0051] The preparation method of the temperature-sensitive grouting material in this embodiment specifically includes the following steps.
[0052] Step 1: Raw material pretreatment.
[0053] The basic cementitious material, aluminum hydroxide flame retardant, and anti-permeability agent were ground to a particle size of less than or equal to 100 μm to obtain the treated basic cementitious material, the treated flame retardant, and the treated anti-permeability agent.
[0054] In step one, the anti-permeability agent is obtained by compounding silica fume and sodium methylsilicate in a mass ratio of 1:1. The particle size of silica fume is less than or equal to 10 μm, and the solid content of sodium methylsilicate is greater than or equal to 30%.
[0055] Step 2: Mix and stir.
[0056] Water, the treated base cementitious material obtained in step one, the treated flame retardant, and the treated anti-permeability agent are added to a planetary mixer and stirred at 200 r / min for 5 min to achieve initial uniform mixing; then polycarboxylate superplasticizer is added and stirring is continued for 3 min; then the prepared grafted modified polyN-isopropylacrylamide, nanocomposite modified thermosensitive polyurethane, low temperature accelerator, and high temperature regulator are added slowly in sequence, the stirring speed is increased to 400 r / min, and stirring is carried out for 15 min to fully disperse and mix the components to obtain a temperature-sensitive grouting material.
[0057] Step two, the preparation method of graft-modified poly(N-isopropylacrylamide), specifically includes the following steps: Poly(N-isopropylacrylamide) with terminal carboxyl or hydroxyl groups is reacted with polyethylene glycol in deionized water as solvent, and dicyclohexylcarbodiimide and 4-dimethylaminopyridine as activators, under nitrogen protection at 40°C for 6 hours to obtain graft-modified poly(N-isopropylacrylamide), denoted as poly(N-isopropylacrylamide-polyethylene glycol); wherein the mass of deionized water added is 5 times the total mass of poly(N-isopropylacrylamide) and polyethylene glycol added; in the activator, the molar ratio of dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 1:0.1; the number average molecular weight of poly(N-isopropylacrylamide) is 5000, the number average molecular weight of polyethylene glycol is 2000, and the grafting rate of polyethylene glycol graft-modified poly(N-isopropylacrylamide) is 85%.
[0058] Step two, the preparation method of poly-N-isopropylacrylamide, specifically includes the following steps: N-isopropylacrylamide monomer and initiator azobisisobutyronitrile are added to solvent water at a mass ratio of 85:1, mixed evenly, and placed in a reaction vessel. Under nitrogen protection, the reaction vessel is placed in a constant temperature water bath at 60°C and refluxed for 10 hours. After the reflux reaction is completed, the solvent is removed from the reaction product by evaporation. Then, the solvent-removed reaction product is dissolved in acetone to obtain an acetone solution. The obtained acetone solution is then added dropwise to n-hexane for precipitation treatment. Subsequently, the product is filtered and dried under vacuum at 30°C for 48 hours to obtain poly-N-isopropylacrylamide.
[0059] Step two, the preparation method of nanocomposite modified thermosensitive polyurethane, specifically includes the following steps: Nano-TiO2 particles are dispersed in anhydrous ethanol, and silane coupling agent KH-550 is added, with the mass of KH-550 being 3% of the mass of the nano-TiO2 particles. The mixture is then reacted at 60℃ and 300 r / min for 2 hours. After the reaction, it is centrifuged and vacuum dried to obtain nano-TiO2 particles modified with KH-550. A polyether polyol with a hydroxyl value of 28 mg KOH / g, toluene diisocyanate, and chain extender ethylene glycol are mixed in a mass ratio of 5:3:1 to obtain a mixed reactant. This mixture is then heated to 80℃ in a nitrogen-protected reactor and reacted at 200 r / min for 3 hours. After 1 hour of reaction, nano-TiO2 particles modified with KH-550 are added, with the nano-TiO2 particles accounting for 2% of the total mass of the mixed reactant, finally yielding the nanocomposite modified thermosensitive polyurethane.
[0060] Step two, the preparation method of the low-temperature accelerator, specifically includes the following steps: Glycerol and organic amine are mixed, then deionized water is added, and the mixture is stirred at 200 r / min at 40℃ until completely dissolved; after dissolution and stirring, nanocellulose whiskers are added, and stirring continues for 30 min to form a uniform sol. The sol shows no obvious crystallization at -20℃, and the viscosity of the sol at 25℃ is 1500 mPa·s. This sol is the low-temperature accelerator. Specifically, during the preparation of the low-temperature accelerator, the mass ratio of glycerol, organic amine, and nanocellulose whiskers is 6:1:1; the length of the nanocellulose whiskers is 100 nm, the diameter is 5 nm, and the specific surface area is greater than or equal to 100 m² / g; the nanocellulose whiskers are nanocellulose whiskers that have undergone ultrasonic dispersion treatment, with an ultrasonic dispersion power of 300 W and an ultrasonic dispersion time of 15 min.
[0061] In step two, the high-temperature regulator is composed of hydroxypropyl methylcellulose, citric acid, and light calcium carbonate in a mass ratio of 3:1:4.
[0062] In step two, the water reduction rate of the polycarboxylate superplasticizer is greater than or equal to 30%, and the number average molecular weight of the polycarboxylate superplasticizer is 50,000.
[0063] In this embodiment, the basic cementitious material is sulfoaluminate cement, which has the characteristics of rapid hardening and early strength. The calcium sulfoaluminate in its mineral composition can react rapidly with water during the hydration process to generate hydration products such as ettringite. It can quickly solidify in the high temperature environment of the coal mine goaf to form an early support structure, which meets the needs of rapid construction of the project.
[0064] In this embodiment, the grafted-modified poly(N-isopropylacrylamide) achieves precise control of its low critical solution temperature to 25–40°C through polyethylene glycol grafting. This temperature-dependent hydrophilic-to-hydrophobic conformational transition of the molecular chains directly controls the slurry viscosity and curing rate. The nanocomposite-modified thermosensitive polyurethane utilizes nano-TiO2 particles modified with the silane coupling agent KH-550 to enhance interfacial bonding. The synergistic effect of the soft and hard segments of the nanocomposite-modified thermosensitive polyurethane extends the material's stability at both high and low temperatures. The synergistic mass ratio of the grafted-modified poly(N-isopropylacrylamide) and the nanocomposite-modified thermosensitive polyurethane constructs an interpenetrating network, allowing the grafted-modified poly(N-isopropylacrylamide) to dominate the mid-temperature response, while the nanocomposite-modified thermosensitive polyurethane enhances extreme temperature performance. This not only resolves the contradiction of traditional materials exhibiting poor low-temperature fluidity and rapid high-temperature solidification in a wide temperature range of -20°C to 60°C, but also achieves improved mechanical properties, increased construction efficiency, and reduced costs.
[0065] In the complex temperature environment of the coal mine goaf, the grouting material of this embodiment exhibits the following characteristics: When the temperature is in the low-temperature range of -20℃ to 25℃, the temperature-sensitive polymer is in a shrinking state, but it enhances the intermolecular hydrogen bonds through hydrophobic segments, assisting the low-temperature accelerator to improve the antifreeze consistency of the grout and avoid segregation. When the temperature rises to the range of 25℃ to 40℃, the hydrophilic-hydrophobic phase transition of the grafted modified poly(N-isopropylacrylamide) triggers the dynamic adjustment of viscosity and curing rate, allowing the grout to smoothly transition from the "antifreeze stable state" to the "construction flow dynamic state". When the temperature exceeds 40℃ and enters the high-temperature range of 40℃ to 60℃, the network structure formed by the temperature-sensitive polymer in the early stage works synergistically with the high-temperature resistant groups in the nanocomposite modified temperature-sensitive polyurethane to inhibit the runaway hydration and material degradation at high temperatures.
[0066] The temperature-sensitive control mechanism of the grouting material in this embodiment lies in the reversible conformational transformation of the grafted modified poly(N-isopropylacrylamide) molecular chain near the low critical solution temperature (LCST): below the LCST, the amide groups form hydrogen bonds with water molecules, causing the molecular chain to stretch and enhancing the fluidity of the grout; above the LCST, the hydrophobic effect of the isopropyl groups causes the molecular chain to shrink, accelerating the cross-linking and curing of the grout.
[0067] In this embodiment, the low critical solution temperature (LCST) of the grafted poly(N-isopropylacrylamide) molecular chain is not a fixed constant; it can be precisely adjusted by changing the molecular weight of the polymer, the ratio of comonomers, and the type of end groups.
[0068] In this embodiment, the phase transition process of the grafted modified poly-N-isopropylacrylamide molecular chain enables the thermosensitive polymer to not only achieve precise control of the rheological properties of the grouting material in the range of 25-40℃, but also extend this control capability to the entire wide temperature range of -20℃ to 60℃ through synergy with antifreeze and high-temperature resistant components. From ensuring fluidity during construction to releasing temperature stress during service, this comprehensively solves the performance failure problem of traditional grouting materials in a wide temperature range environment.
[0069] In this embodiment, grafted-modified poly(N-isopropylacrylamide) and nanocomposite-modified thermosensitive polyurethane form a semi-interpenetrating network through physical entanglement. The nanocomposite-modified thermosensitive polyurethane forms a rigid framework through chemical crosslinking (with nano-TiO2 particles as crosslinking points), while the physically crosslinked network of grafted-modified poly(N-isopropylacrylamide) (relying on hydrogen bonds and chain entanglement) permeates the modified polyurethane framework, forming a "network within a network" structure. This structure achieves a balance between network stability and dynamic responsiveness through the interpenetration of the molecular chains of the two polymers and the interfacial reinforcement of the nanoparticles. The grafted-modified poly(N-isopropylacrylamide) provides temperature responsiveness, the nanocomposite-modified thermosensitive polyurethane imparts mechanical toughness, and the nano-TiO2 particles act as reinforcing points to inhibit excessive chain segment movement, thereby maintaining the integrity of the grouting material structure within the temperature range of -20℃ to 60℃.
[0070] In this embodiment, during the preparation of graft-modified poly(N-isopropylacrylamide), a catalytic system of dicyclohexylcarbodiimide and 4-dimethylaminopyridine is used to promote the esterification / etherification grafting reaction between poly(N-isopropylacrylamide) with terminal carboxyl / hydroxyl groups and polyethylene glycol under nitrogen protection. The role of dicyclohexylcarbodiimide is to activate the carboxylic acid group as a dehydrating agent, and 4-dimethylaminopyridine is to accelerate the acyl group transfer as a nucleophilic catalyst, so that the polyethylene glycol chain segment is efficiently grafted to the poly(N-isopropylacrylamide) molecular chain.
[0071] In this embodiment, during the preparation of nanocomposite modified thermosensitive polyurethane, firstly, silane coupling agent KH-550 introduces amino groups onto the surface of nano-TiO2 particles through a hydrolysis-condensation reaction, enabling the nano-TiO2 particles to be uniformly dispersed and form a strong interfacial bond with the polyurethane matrix. Secondly, polyether polyol provides soft segments to impart thermosensitive swelling properties, while toluene diisocyanate or hexamethylene diisocyanate, along with chain extenders ethylene glycol or 1,4-butanediol, form hard segments to regulate crystallinity and match the phase transition range of poly(N-isopropylacrylamide). Finally, nano-TiO2 particles modified with silane coupling agent KH-550 are introduced in the middle stage of polyurethane synthesis. The amino groups on the surface of the nano-TiO2 particles modified with silane coupling agent KH-550 participate in the isocyanate reaction, forming a nano-reinforced network.
[0072] In this embodiment, the low-temperature accelerator, in a low-temperature environment (-20℃), utilizes glycerol to inhibit ice crystal formation by lowering the freezing point of the system, thus providing a fundamental guarantee for the fluidity of the grouting material. Although nanocellulose whiskers have a thickening tendency, in this formulation, they are ultrasonically dispersed to form a uniformly dispersed nanoscale phase. Furthermore, the small proportion of nanocellulose crystals in the low-temperature accelerator prevents the formation of a continuous network structure at low concentrations. At low temperatures, the role of nanocellulose crystals is manifested in two ways: firstly, by adsorbing free water molecules through high specific surface area and hydrophilicity, they reduce the damage of ice crystals to the dispersion of sulfoaluminate cement particles, indirectly maintaining the fluidity of the grout; secondly, their surface hydroxyl groups form hydrogen bonds with glycerol molecules, synergistically inhibiting the agglomeration of sulfoaluminate cement particles, thereby alleviating the grout segregation problem that might be caused by glycerol alone; simultaneously, nanocellulose whiskers, by bonding with calcium ions generated in the early stages of sulfoaluminate cement hydration, promote the low-temperature hydration reaction while avoiding the loss of fluidity caused by a sudden increase in viscosity in traditional thickeners, achieving a synergistic effect of antifreeze, fluid retention, and strength promotion.
[0073] In this embodiment, when exposed to a fire source or high temperature, the aluminum hydroxide flame retardant decomposes upon heating, absorbing a large amount of heat and lowering the ambient temperature. At the same time, the released water vapor dilutes the oxygen concentration, thus playing a role in cooling and flame retardancy.
[0074] In this embodiment, sodium methylsilicate in the anti-permeability agent forms a hydrophobic film on the surface of the material, making it difficult for water molecules to enter the interior of the grouting material, significantly improving the impermeability of the grouting material, effectively resisting the erosion of groundwater in the goaf area, and extending the service life of the grouting body.
[0075] In this embodiment, the molecular chains of the polycarboxylate superplasticizer are adsorbed onto the surface of sulfoaluminate cement particles, generating strong electrostatic repulsion and steric hindrance, which disperses the sulfoaluminate cement particles, increases the fluidity of the temperature-sensitive grouting material, reduces water consumption, and improves the strength and durability of the temperature-sensitive grouting material.
[0076] In this embodiment, aluminum hydroxide flame retardant and high-temperature regulator synergistically suppress the temperature rise caused by spontaneous combustion of coal, while anti-permeability agent and temperature-sensitive polymer jointly enhance the material density of the temperature-sensitive grouting material, and polycarboxylate superplasticizer ensures the pumpability of the grout in low-temperature environments. By improving overall performance while avoiding antagonistic effects between components, the service life of the temperature-sensitive grouting material in complex coal mine environments is extended, achieving a multi-objective balance of flame retardancy, anti-permeability, and workability.
[0077] Example 2: This embodiment provides a temperature-sensitive grouting material, which is made from the following raw materials by weight: 45% sulfoaluminate cement, 15% grafted modified poly(N-isopropylacrylamide), 8% nanocomposite modified thermosensitive polyurethane, 6% low-temperature accelerator, 5% high-temperature regulator, 6% aluminum hydroxide flame retardant, 4% anti-permeability agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the weight parts of the raw materials being 100%.
[0078] The total mass of the raw materials for the temperature-sensitive grouting material in this embodiment is the same as the total mass of the raw materials for the temperature-sensitive grouting material in Example 1.
[0079] The preparation method of the temperature-dependent grouting material in this embodiment is basically the same as that in Example 1, the only difference being: In step two, the mixing speed of the planetary mixer is changed to 300 r / min and the mixing time is changed to 8 min when water, the treated base cementitious material, the treated flame retardant and the treated impermeable agent are added; the mixing time is changed to 5 min when polycarboxylate superplasticizer is added; the mixing speed is changed to 500 r / min and the mixing time is changed to 20 min after grafted modified poly-N-isopropylacrylamide, nanocomposite modified thermosensitive polyurethane, low temperature accelerator and high temperature regulator are added.
[0080] In step two, during the preparation of graft-modified poly(N-isopropylacrylamide), the reaction temperature was changed to 60℃, the reaction time was changed to 12h, the mass of deionized water added as solvent was 10 times the total mass of poly(N-isopropylacrylamide) and polyethylene glycol added, the molar ratio of dicyclohexylcarbodiimide and 4-dimethylaminopyridine in the activator was changed to 1:0.2, the number average molecular weight of poly(N-isopropylacrylamide) was changed to 10000, the number average molecular weight of polyethylene glycol was changed to 5000, and the grafting rate of poly(N-isopropylacrylamide) grafted with polyethylene glycol was 90%.
[0081] In step two, during the preparation of poly-N-isopropylacrylamide, the mass ratio of N-isopropylacrylamide monomer to initiator azobisisobutyronitrile was changed to 90:1, the reflux reaction temperature was changed to 60℃, the reflux reaction time was changed to 10h, the temperature of the solid product during vacuum drying was changed to 25℃, and the vacuum drying time was changed to 36h.
[0082] In step two, during the preparation of the nanocomposite modified thermosensitive polyurethane, the mass of the silane coupling agent KH-550 was changed to 5% of the mass of the nano TiO2 particles; the reaction temperature after adding the silane coupling agent KH-550 was changed to 70℃; the stirring speed was 400 r / min; and the stirring time was 3 h. The hydroxyl value of the polyether polyol was changed to 56 mg KOH / g; the mass ratio of the polyether polyol, toluene diisocyanate, and chain extender ethylene glycol was 7:4:2; the reaction temperature of the mixed reactants was changed to 90℃; the stirring speed was changed to 300 r / min; and the reaction time of the mixed reactants was changed to 5 h. The nano TiO2 particles accounted for 5% of the total mass of the mixed reactants.
[0083] In step two, during the preparation of the low-temperature accelerator, the stirring temperature after mixing glycerol and organic amine was changed to 60℃, and the stirring speed was changed to 300 r / min; the stirring time after adding nanocellulose whiskers was changed to 40 min, and the viscosity of the sol at 25℃ was changed to 3000 mPa·s.
[0084] In step two, during the preparation of the low-temperature accelerator, the mass ratio of glycerol, organic amine, and nanocellulose whiskers was changed to 8:2:2, the length of the nanocellulose whiskers was changed to 500 nm, the diameter was changed to 20 nm, the power of the ultrasonic dispersion treatment of the nanocellulose whiskers was changed to 500 W, and the ultrasonic dispersion treatment time was changed to 10 min.
[0085] In step two, the mass ratio of hydroxypropyl methylcellulose, citric acid, and light calcium carbonate is changed to 4:2:6 when the high-temperature regulator is prepared.
[0086] Example 3: This embodiment provides a temperature-sensitive grouting material, which is made from the following raw materials by weight: 50% sulfoaluminate cement, 10% grafted modified poly(N-isopropylacrylamide), 5% nanocomposite modified thermosensitive polyurethane, 4% low-temperature accelerator, 3% high-temperature regulator, 10% aluminum hydroxide flame retardant, 7% anti-permeability agent, 3% polycarboxylate superplasticizer, and the balance being water, with the sum of the weight parts of the raw materials being 100%.
[0087] The total mass of the raw materials for the temperature-sensitive grouting material in this embodiment is the same as the total mass of the raw materials for the temperature-sensitive grouting material in Example 1.
[0088] The preparation method of the temperature-dependent grouting material in this embodiment is basically the same as that in Example 1, the only difference being: In step two, the mixing speed of the planetary mixer was changed to 250 r / min and the mixing time was changed to 6 min when water, the treated base cementitious material, the treated flame retardant, and the treated anti-permeability agent were added; the mixing time was changed to 4 min after adding the polycarboxylate superplasticizer; and the mixing speed was changed to 450 r / min and the mixing time was changed to 18 min after adding the grafted modified poly(N-isopropylacrylamide), nanocomposite modified thermosensitive polyurethane, low temperature accelerator, and high temperature regulator.
[0089] In step two, during the preparation of the grafted poly(N-isopropylacrylamide), the reaction temperature was changed to 50℃, the reaction time was changed to 10h, the mass of deionized water added as solvent was 8 times the total mass of poly(N-isopropylacrylamide) and polyethylene glycol added, the molar ratio of dicyclohexylcarbodiimide and 4-dimethylaminopyridine in the activator was changed to 1:0.15, the number average molecular weight of poly(N-isopropylacrylamide) was changed to 8000, the number average molecular weight of polyethylene glycol was changed to 3000, and the grafting rate of poly(N-isopropylacrylamide) grafted with polyethylene glycol was 92%.
[0090] In step two, during the preparation of poly-N-isopropylacrylamide, the mass ratio of N-isopropylacrylamide monomer to initiator azobisisobutyronitrile was changed to 100:1, the reflux reaction temperature was changed to 65℃, the reflux reaction time was changed to 12h, the temperature of the solid product during vacuum drying was changed to 35℃, and the vacuum drying time was changed to 24h.
[0091] In step two, during the preparation of the nanocomposite modified thermosensitive polyurethane, the mass of silane coupling agent KH-550 was changed to 4% of the mass of nano-TiO2 particles; the reaction temperature after adding silane coupling agent KH-550 was changed to 65℃; the stirring speed was 350 r / min; the hydroxyl value of the polyether polyol was changed to 40 mg KOH / g; the mass ratio of polyether polyol, toluene diisocyanate, and chain extender ethylene glycol was 6:4:1; the reaction temperature of the mixed reactants was changed to 85℃; the stirring speed was changed to 250 r / min; and the reaction time of the mixed reactants was changed to 4 h. After the reaction had proceeded for 2 h, nano-TiO2 particles modified with silane coupling agent KH-550 were added, with the nano-TiO2 particles accounting for 4% of the total mass of the mixed reactants.
[0092] In step two, during the preparation of the low-temperature accelerator, the stirring temperature after mixing glycerol and organic amine was changed to 50℃, the stirring speed was changed to 300 r / min, the stirring time after adding nanocellulose whiskers was changed to 35 min, and the viscosity of the sol at 25℃ was changed to 2000 mPa·s.
[0093] In step two, during the preparation of the low-temperature accelerator, the mass ratio of glycerol, organic amine, and nanocellulose whiskers was changed to 7:1.5:1.5, the length of the nanocellulose whiskers was changed to 400 nm, the diameter was changed to 10 nm, the power of the ultrasonic dispersion treatment of the nanocellulose whiskers was changed to 400 W, and the ultrasonic dispersion treatment time was changed to 12 min.
[0094] In step two, the mass ratio of hydroxypropyl methylcellulose, citric acid, and light calcium carbonate is changed to 3.5:1.5:5 when the high-temperature regulator is prepared.
[0095] Comparative Example 1: (The proportion of sulfoaluminate cement was changed and no temperature-sensitive polymer was added) This comparative example provides a grouting material, which, by weight, is made of the following raw materials: 71% sulfoaluminate cement, 5% temperature-responsive additives (specifically, 3% low-temperature accelerator and 2% high-temperature regulator), 5% aluminum hydroxide flame retardant, 3% anti-permeability agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the weight parts of the raw materials being 100%.
[0096] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0097] The preparation method of the grouting material in this comparative example is basically the same as the preparation method of the temperature-sensitive grouting material in Example 1. The only difference is that no temperature-sensitive polymer is prepared or added in step two, and the amount of sulfoaluminate cement and water added in step two is changed.
[0098] In the preparation method of the grouting material in this comparative example, the amounts of sulfoaluminate cement, thermosensitive polymer, and water added are consistent with the raw material composition of the grouting material in this comparative example.
[0099] Comparative Example 2: (Thermosensitive polymer contains only grafted modified poly(N-isopropylacrylamide)) This comparative example provides a grouting material, which, by weight, is made from the following raw materials: 60% sulfoaluminate cement, 11% thermosensitive polymer (specifically, 11% grafted modified poly(N-isopropylacrylamide)), 5% temperature-responsive additive (specifically, 3% low-temperature accelerator and 2% high-temperature regulator), 5% aluminum hydroxide flame retardant, 3% impermeable agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the weight parts of the raw materials being 100%.
[0100] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0101] The preparation method of the grouting material in this comparative example is basically the same as that of the temperature-sensitive grouting material in Example 1. The only difference is that: in step two, no nanocomposite modified temperature-sensitive polyurethane is prepared or added, and the amount of grafted modified polyN-isopropylacrylamide and water added in step two is changed.
[0102] In the preparation method of the grouting material in this comparative example, the amounts of grafted modified poly(N-isopropylacrylamide), nanocomposite modified thermosensitive polyurethane, and water added are consistent with the raw material composition of the grouting material in this comparative example.
[0103] Comparative Example 3: (Thermosensitive polymers only include nanocomposite modified thermosensitive polyurethane) This comparative example provides a grouting material, which, by weight, is made of the following raw materials: 60% sulfoaluminate cement, 11% thermosensitive polymer (specifically, 11% nanocomposite modified thermosensitive polyurethane), 5% temperature-responsive additive (specifically, 3% low-temperature accelerator and 2% high-temperature regulator), 5% aluminum hydroxide flame retardant, 3% anti-permeability agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the weight parts of the raw materials being 100%.
[0104] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0105] The preparation method of the grouting material in this comparative example is basically the same as that of the temperature-sensitive grouting material in Example 1. The only difference is that in step two, no grafted modified poly(N-isopropylacrylamide) is prepared or added, and the amount of nanocomposite modified temperature-sensitive polyurethane and water added in step two is changed.
[0106] In the preparation method of the grouting material in this comparative example, the amounts of grafted modified poly(N-isopropylacrylamide), nanocomposite modified thermosensitive polyurethane, and water added are consistent with the raw material composition of the grouting material in this comparative example.
[0107] Comparative Example 4: (without temperature-responsive additives) This comparative example provides a grouting material, which is temperature-sensitive and is made from the following raw materials by weight: 60% basic cementitious material, i.e., sulfoaluminate cement; 11% temperature-sensitive polymer (specifically, 8% grafted modified poly(N-isopropylacrylamide) and 3% nanocomposite modified temperature-sensitive polyurethane); 5% aluminum hydroxide flame retardant; 3% anti-permeability agent; 1% polycarboxylate superplasticizer; and the balance being water. The sum of the weight parts of the raw materials is 100%.
[0108] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0109] The preparation method of the grouting material in this comparative example is basically the same as the preparation method of the temperature-responsive grouting material in Example 1, the only difference being that no temperature-responsive additives are prepared or added in step two.
[0110] In the preparation method of the grouting material in this comparative example, the amount of temperature-responsive additive and water added is consistent with the raw material composition of the grouting material in this comparative example.
[0111] Comparative Example 5: (The poly-N-isopropylacrylamide in the thermosensitive polymer was not grafted) This comparative example provides a grouting material, which is temperature-sensitive and is made from the following raw materials by weight: 60% basic cementitious material, i.e., sulfoaluminate cement; 11% temperature-sensitive polymer (specifically, 8% poly(N-isopropylacrylamide) and 3% nanocomposite modified temperature-sensitive polyurethane); 5% temperature-responsive additive (specifically, 3% low-temperature accelerator and 2% high-temperature regulator); 5% aluminum hydroxide flame retardant; 3% impermeable agent; 1% polycarboxylate superplasticizer; and the balance being water. The total weight of the raw materials is 100%.
[0112] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0113] The preparation method of the grouting material in this comparative example is basically the same as the preparation method of the temperature-sensitive grouting material in Example 1. The only difference is that ungrafted modified polyN-isopropylacrylamide is added in step two.
[0114] Comparative Example 6: (The poly-N-isopropylacrylamide in the thermo-sensitive polymer is not grafted, and the thermo-sensitive polyurethane in the thermo-sensitive polymer is polyurethane that has not undergone nanocomposite modification.) This comparative example provides a grouting material, which is temperature-sensitive and is made from the following raw materials by weight: 60% basic cementitious material, i.e., sulfoaluminate cement; 11% temperature-sensitive polymer (specifically, 8% poly(N-isopropylacrylamide) and 3% polyurethane); 5% temperature-responsive additive (specifically, 3% low-temperature accelerator and 2% high-temperature regulator); 5% aluminum hydroxide flame retardant; 3% impermeable agent; 1% polycarboxylate superplasticizer; and the balance being water. The sum of the weight parts of the raw materials is 100%.
[0115] In this comparative example, step two, the preparation method of polyurethane, specifically includes the following steps: a polyether polyol with a hydroxyl value of 28 mg KOH / g and an average functionality of 3, toluene diisocyanate, and chain extender ethylene glycol are mixed in a mass ratio of 5:3:1 to obtain a mixed reactant. Then, in a nitrogen-protected reactor, the temperature is raised to 80°C, and the mixed reactant is reacted for 3 hours with a stirring speed of 200 r / min to finally obtain polyurethane, which is a polyurethane without nanocomposite modification.
[0116] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0117] The preparation method of the grouting material in this comparative example is basically the same as that of the temperature-sensitive grouting material in Example 1. The only difference is that in step two, ungrafted modified polyN-isopropylacrylamide and unmodified polyurethane are added.
[0118] Comparative Example 7: (Changing the raw material ratio) This comparative example provides a grouting material, which is temperature-sensitive and is made from the following raw materials by weight: 70% sulfoaluminate cement, 3% temperature-sensitive polymer (specifically, 2% grafted modified poly(N-isopropylacrylamide) and 1% nanocomposite modified temperature-sensitive polyurethane), 3% temperature-responsive additive (specifically, 2% low-temperature accelerator and 1% high-temperature regulator), 5% aluminum hydroxide flame retardant, 3% anti-permeability agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the raw materials being 100% by weight.
[0119] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0120] The preparation method of the grouting material in this comparative example is basically the same as the preparation method of the temperature-sensitive grouting material in Example 1, the only difference being the change in the amount of each raw material added to the grouting material.
[0121] In the preparation method of the grouting material in this comparative example, the amount of each raw material added to the grouting material is consistent with the raw material composition of the grouting material in this comparative example.
[0122] Comparative Example 8: (Changing the raw material ratio) This comparative example provides a grouting material, which is temperature-sensitive and is made from the following raw materials by weight: 40% sulfoaluminate cement, 30% thermosensitive polymer (specifically, 20% grafted modified poly(N-isopropylacrylamide) and 10% nanocomposite modified thermosensitive polyurethane), 15% temperature-responsive additive (specifically, 8% low-temperature accelerator and 7% high-temperature regulator), 1% aluminum hydroxide flame retardant, 2% impermeable agent, 1% polycarboxylate superplasticizer, and the balance being water, with the sum of the raw materials being 100% by weight.
[0123] The total mass of raw materials for the grouting material in this comparative example is the same as the total mass of raw materials for the temperature-sensitive grouting material in Example 1.
[0124] The preparation method of the grouting material in this comparative example is basically the same as the preparation method of the temperature-sensitive grouting material in Example 1, the only difference being the change in the amount of each raw material added to the grouting material.
[0125] In the preparation method of the grouting material in this comparative example, the amount of each raw material added to the grouting material is consistent with the raw material composition of the grouting material in this comparative example.
[0126] Table 1 Comparison of performance parameters of grouting materials at 25℃
[0127] At the same temperature (25°C), the 28-day compressive strength, flexural strength, fluidity, initial setting time, and impermeability grade of Examples 1 to 3 and Comparative Examples 1 to 8 were compared to confirm the superiority or inferiority of the formulation (i.e., raw material composition) of the temperature-sensitive grouting material in Examples 1 to 3 of this application compared with the formulation in Comparative Examples 1 to 8.
[0128] As shown in Table 1 above, the 28-day compressive strength of the temperature-responsive grouting materials in Examples 1 to 3 is between 40 and 45 MPa, significantly higher than that of most comparative examples. The grouting material in Comparative Example 1, lacking the addition of a temperature-sensitive polymer, has a 28-day compressive strength of only 30 MPa. The grouting materials in Comparative Examples 2 and 3, due to the absence of the temperature-sensitive polymer component, also have lower 28-day compressive strengths than Examples 1 to 3. The grouting material in Comparative Example 4 lacks temperature-responsive additives, affecting its 28-day compressive strength. The poly(N-isopropylacrylamide) in Comparative Example 5, without graft modification, results in a 28-day compressive strength lower than that of Examples 1 to 3. Comparative Example 6 uses unmodified polyurethane, and its 28-day compressive strength is lower than that of Examples 1 to 3. In Comparative Example 7, the amount of temperature-sensitive polymer added was insufficient, and the 28-day compressive strength of the grouting material was not as good as that of Examples 1 to 3. In Comparative Example 8, although the amount of temperature-sensitive polymer added was higher than that of Examples 1 to 3, the improvement effect on the 28-day compressive strength of the grouting material was not obvious, and it may bring other potential problems.
[0129] The flexural strength of the temperature-dependent grouting materials in Examples 1 to 3 is between 7 and 8.5 MPa, which is also higher than that of most comparative examples. The flowability of the temperature-dependent grouting materials in Examples 1 to 3 is between 280 and 300 mm, which is quite good.
[0130] The initial setting time of the temperature-dependent grouting materials in Examples 1 to 3 is between 100 and 120 minutes, and the final setting time is between 200 and 240 minutes, which is reasonable and conducive to construction operations.
[0131] The temperature-dependent grouting materials in Examples 1 to 3 have a water resistance rating between P10 and P12, indicating good waterproofing performance. The grouting materials in Comparative Examples 1 to 7 have a water resistance rating between P6 and P8, indicating poor water resistance. Comparative Example 8 has the lowest water resistance rating, at only P5.
[0132] The performance changes of the grouting materials obtained in Examples 1 to 3 and Comparative Examples 1 to 8 at four temperature points of -20℃, 25℃, 40℃ and 60℃ were compared to confirm the variation of the four properties of the prepared grouting materials—flowability, initial setting time, 28-day compressive strength and impermeability grade—with temperature. The "temperature response" characteristics of the grouting materials obtained in Examples 1 to 3 and Comparative Examples 1 to 8 were investigated respectively, and the specific results are shown in Table 2.
[0133] Table 2. Comparison of performance parameters of grouting materials in the examples and comparative examples at different temperatures.
[0134] Analyzing the data in Table 2, we can draw the following conclusions: First, performance comparison at low temperatures (-20℃): In Examples 1 to 3, at -20°C, the fluidity of the temperature-sensitive grouting material remained at 190–210 mm, the initial setting time was 180–200 min, the 28-day compressive strength was 34–36 MPa, and the impermeability grade was P9–P10. This was due to the glycerol in the low-temperature accelerator lowering the freezing point, the nanocellulose whiskers inhibiting ice crystal growth, and the hydrogen bond network formed by the hydrophobic segments of the temperature-sensitive polymer, which effectively maintained the fluidity and early strength development of the grout.
[0135] In contrast, compared to Comparative Examples 1 to 8, due to insufficient types and amounts of raw materials, the fluidity of the grouting materials at -20℃ was generally lower than 180mm (the fluidity of the grouting material in Comparative Example 8 was only 145mm), the initial setting time was as long as 250-310min, the curing was too slow, the 28-day compressive strength was only 20-30MPa, and the impermeability grade was P4-P6, which could not meet the construction and support requirements in low-temperature environments.
[0136] Second, performance comparison at medium temperatures (i.e., 25℃ and 40℃): At 25℃, the fluidity of the temperature-responsive grouting materials in Examples 1 to 3 reached 280–300 mm, with an initial setting time of 100–120 min, falling within the optimal construction range. Furthermore, the 28-day compressive strength was 40–45 MPa, and the impermeability grade was P10–P12. This is because the grafted poly(N-isopropylacrylamide) molecular chains expanded below the LCST, enhancing grout fluidity. Simultaneously, the temperature-responsive additives did not trigger regulation, ensuring ease of construction.
[0137] At 40°C, the fluidity of the temperature-sensitive grouting materials in Examples 1 to 3 decreased to 230–250 mm, but they were still pumpable. The initial setting time was shortened to 60–70 min, allowing for rapid curing at high temperatures, and the compressive strength increased to 43–47 MPa. This is because the grafted poly(N-isopropylacrylamide) undergoes hydrophobic shrinkage when the temperature exceeds the LCST, accelerating cross-linking and curing. At the same time, the high-temperature regulator begins to act, avoiding strength loss caused by rapid setting.
[0138] However, the grouting materials of Comparative Examples 1 to 8 exhibited significant performance fluctuations in the mid-temperature range: at 25°C, the fluidity was generally below 270 mm; at 40°C, the fluidity dropped sharply (only 180 mm in Comparative Example 1), with either excessively long (affecting efficiency) or excessively short (easily clogging pipes). The 28-day compressive strength of the grouting materials at 40°C was lower than that of Examples 1 to 3, highlighting the precise control of the raw material types and proportions in Examples 1 to 3 within the mid-temperature range.
[0139] Third, performance comparison at high temperatures (60℃): At 60℃, the fluidity of the temperature-sensitive grouting materials in Examples 1 to 3 remained at 200–220 mm, the initial setting time was 40–50 min, the 28-day compressive strength was 38–41 MPa, and the impermeability grade was P9–P11. This is attributed to the high-temperature resistant network formed by the nanocomposite modified temperature-sensitive polyurethane, the gelling effect of hydroxypropyl methylcellulose in the high-temperature regulator, and the regulation of the hydration process by citric acid, which effectively suppressed hydration runaway and material degradation at high temperatures.
[0140] The grouting materials of Comparative Examples 1 to 8 showed severe performance degradation at 60℃: the fluidity was generally less than 150mm (comparative Example 1 was only 120mm), the initial setting time was mostly 30-35min (rapid setting led to loose structure), the 28d compressive strength was only 18-28MPa, and the impermeability grade was P3-P6, which could not withstand the long-term support pressure under high temperature environment.
Claims
1. A temperature-sensitive grouting material, characterized in that, The temperature-responsive grouting material is made from the following raw materials by weight: 45%–60% base cementitious material, 11%–23% temperature-sensitive polymer, 5%–11% temperature-responsive additive, 5%–10% flame retardant, 3%–7% anti-permeability agent, 1%–3% water-reducing agent, and the balance being water. The sum of the weight parts of the raw materials is 100%. The basic cementitious material includes sulfoaluminate cement; The thermosensitive polymers include grafted modified poly(N-isopropylacrylamide) and nanocomposite modified thermosensitive polyurethane. The grafted modified poly-N-isopropylacrylamide is prepared by grafting polyethylene glycol onto poly-N-isopropylacrylamide. The poly-N-isopropylacrylamide has a carboxyl or hydroxyl group at its end, and the low critical dissolution temperature of the grafted modified poly-N-isopropylacrylamide is 25-40°C. The nanomaterial used in the preparation of the nanocomposite modified thermosensitive polyurethane is nano-TiO2 particles; The temperature-responsive additives include low-temperature accelerators and high-temperature regulators.
2. The temperature-sensitive grouting material as described in claim 1, characterized in that, The temperature-sensitive grouting material is made from the following raw materials by weight: 60% basic cementitious material, 11% temperature-sensitive polymer, 5% temperature-responsive additive, 5% flame retardant, 3% anti-permeability agent, 1% water-reducing agent, and the balance is water, with the total weight of the raw materials being 100%.
3. A method for preparing a temperature-sensitive grouting material as described in any one of claims 1 to 2, characterized in that, The method specifically includes the following steps: Step 1, Raw material pretreatment: The basic cementitious material, flame retardant, and anti-permeability agent are ground to a particle size of less than or equal to 100 μm to obtain the treated basic cementitious material, the treated flame retardant, and the treated anti-permeability agent. Step 2, Mix and stir: Add water, the treated base cementitious material obtained in step one, the treated flame retardant, and the treated impermeable agent to a planetary mixer and stir at a speed of 200-300 r / min for 5-8 min; then add water-reducing agent and continue stirring for 3-5 min; then add grafted modified polyN-isopropylacrylamide, nanocomposite modified thermosensitive polyurethane, low-temperature accelerator, and high-temperature regulator in sequence, increase the stirring speed to 400-500 r / min, and stir for 15-20 min to obtain a temperature-sensitive grouting material.
4. The method for preparing the temperature-sensitive grouting material as described in claim 3, characterized in that, Step two, the preparation method of the grafted modified poly-N-isopropylacrylamide, specifically includes the following steps: Poly-N-isopropylacrylamide with terminal carboxyl or hydroxyl groups was reacted with polyethylene glycol in water or N,N-dimethylformamide as solvent and dicyclohexylcarbodiimide and 4-dimethylaminopyridine as activators under nitrogen protection at 40-60°C for 6-12 hours to obtain grafted modified poly-N-isopropylacrylamide. The mass of the solvent added is 5 to 10 times the total mass of poly(N-isopropylacrylamide) and polyethylene glycol added; In the activator, the molar ratio of dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 1:(0.1-0.2).
5. The method for preparing the temperature-sensitive grouting material as described in claim 4, characterized in that, The preparation method of the aforementioned poly-N-isopropylacrylamide specifically includes the following steps: N-isopropylacrylamide monomer and initiator azobisisobutyronitrile were added to the solvent, mixed evenly, and then placed in a reaction vessel. Under nitrogen protection, the reaction vessel was placed in a constant temperature water bath at 50-65℃ and refluxed for 8-12 hours. After the reflux reaction is completed, the solvent is removed from the reaction product by evaporation. Then, the solvent-removed reaction product is dissolved in acetone to obtain an acetone solution. The obtained acetone solution is then added dropwise to n-hexane for precipitation. After filtration, the solid product obtained by filtration is dried in a vacuum environment at 25-35°C for 24-48 hours to obtain poly-N-isopropylacrylamide.
6. The method for preparing the temperature-sensitive grouting material as described in claim 3, characterized in that, Step two, the preparation method of the nanocomposite modified thermosensitive polyurethane, specifically includes the following steps: Nano-TiO2 particles were dispersed in anhydrous ethanol, and silane coupling agent KH-550 was added. The mass of silane coupling agent KH-550 was 3% to 5% of the mass of nano-TiO2 particles. The mixture was then reacted at 60 to 70°C and 300 to 400 r / min for 2 to 3 hours. After the reaction was completed, the mixture was centrifuged and vacuum dried to obtain nano-TiO2 particles modified with silane coupling agent KH-550. Polyether polyol, isocyanate, and chain extender are mixed in a mass ratio of (5-7):(3-4):(1-2) to obtain a mixed reactant. Then, in a nitrogen-protected reactor, the mixture is heated to 80-90°C and stirred at a stirring speed of 200-300 r / min for 3-5 h. After 1-2 h of reaction, nano-TiO2 particles modified with silane coupling agent KH-550 are added. The nano-TiO2 particles account for 2%-5% of the total mass of the mixed reactant. Finally, nano-composite modified thermosensitive polyurethane is obtained.
7. The method for preparing the temperature-sensitive grouting material as described in claim 3, characterized in that, Step two, the preparation method of the low-temperature accelerator, specifically includes the following steps: Glycerol and organic amine are mixed in a certain proportion, then water is added, and the mixture is stirred at 200-300 r / min at 40-60°C until completely dissolved. After dissolving and stirring, add nano-cellulose whiskers and continue stirring for 30-40 minutes to form a uniform sol. The sol does not crystallize significantly at -20℃ and has a viscosity of 1500-3000 mPa·s at 25℃. This sol is the low-temperature accelerator.
8. The method for preparing the temperature-sensitive grouting material as described in claim 7, characterized in that, In the preparation of the low-temperature accelerator, the mass ratio of glycerol, organic amine and nanocellulose whiskers is (60-80):(10-20):(10-20). The nanocellulose whiskers have a length of 100–500 nm, a diameter of 5–20 nm, and a specific surface area greater than or equal to 100 m² / g. The nanocellulose whiskers are nanocellulose whiskers that have undergone ultrasonic dispersion treatment. The ultrasonic dispersion treatment power is 300-500W and the ultrasonic dispersion treatment time is 10-15min.
9. The method for preparing the temperature-sensitive grouting material as described in claim 3, characterized in that, In step two, the raw materials for preparing the high-temperature regulator include hydroxypropyl methylcellulose, citric acid and light calcium carbonate, and the mass ratio of hydroxypropyl methylcellulose, citric acid and light calcium carbonate is (3-4):(1-2):(4-6).
10. The method for preparing the temperature-sensitive grouting material as described in claim 3, characterized in that, In step one, the flame retardant includes one or more of aluminum hydroxide and magnesium hydroxide; In step one, the impermeable agent is obtained by compounding silica fume and sodium methylsilicate, and the solid content of sodium methylsilicate is greater than or equal to 30%. In step two, the water-reducing agent is a polycarboxylate-based water-reducing agent with a water reduction rate of 30% or greater.
Citation Information
Patent Citations
Anti-seepage method for mine underground reservoirs
CN102767395B
A multi-layer grouting method for seepage prevention and reinforcement of underground reservoirs and dams in coal mines.
CN107237651B
An anti-seepage system for the dam of underground reservoir in coal mine
CN114033489B